PENANAMAN NILAI KARAKTER PEDULI LINGKUNGAN MELALUI PEMBELAJARAN GEOGRAFI DI MADRASAH ALIYAH - Ilmi Firdausi Nuzula (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to describe the instillation of environmental care character values through Geography learning and to identify the supporting and inhibiting factors at MA Ahmad Yani Jabung Malang, a madrasah located in an industrial area. The research uses a qualitative method with a case study approach. Data were collected through participatory observation, in-depth interviews with Geography teachers, homeroom teachers, and students, as well as document analysis of teaching modules, schedules, and activity photographs. The findings reveal that the instillation of environmental care character values is carried out through three stages: planning through the development of teaching modules that integrate environmental care values; implementation using lectures, group discussions, presentations, and the habituation of the